“Beached and commercial plastics’ leachates: Assessment of chemical composition and ecotoxicity to marine biota” - C. Mazzoli; L. Pittura; G. d’Errico; F. Iezzi; D. Fattorini; M. Di Carlo; A. Nardi; M. Mezzelani; M. Benedetti; S. Gorbi; F. Regoli (Journal of Hazardous Materials, 2026)

Structural controls on simultaneous earthquake clustering and normal fault synchronization - F. Iezzi; C. Sgambato; G. Roberts; Z. Mildon; J. Robertson; J. Faure Walker; I. Papanikolaou; A.M. Michetti; S. Mitchell; R. Shanks; R. Phillips; K.J.W. McCaffrey; et al. (Earth and Planetary Science Letters, 2025)

Characteristics and modelling of slip-rate variability and temporal earthquake clustering across a distributed network of active normal faults constrained by in situ 36Cl cosmogenic dating of fault scarp exhumation, central Italy - G.P. Roberts; F. Iezzi; C. Sgambato; J. Robertson; J. Beck; Z.K. Mildon; I. Papanikolaou; A.M. Michetti; J.P. Faure Walker; S. Mitchell; M. Meschis; R. Shanks; et al. (Journal of Structural Geology, 2025)

Geophysical, geochemical, and structural investigations of natural non-volcanic degassing in Oliveto Citra area (southern Apennines): Understandings of structural controls on CO2 leakage - S. Vitale; M.G. Di Giuseppe; C. Fabozzi; S. Albanese; M. Ambrosino; D. Cicchella; C. De Paola; F. Iezzi; R. Isaia; J. Natale; F. Pagliara; A. Troiano; et al. (Marine and Petroleum Geology, 2025)

Spatial migration of temporal earthquake clusters driven by the transfer of differential stress between neighbouring fault/shear-zone structures - G.P. Roberts; C. Sgambato; Z.K. Mildon; F. Iezzi; J. Beck; J. Robertson; I. Papanikolaou; A.M. Michetti; J.P. Faure Walker; M. Meschis; R. Shanks; R. Phillips; et al. (Journal of Structural Geology, 2024)

Slip localization on multiple fault splays accommodating distributed deformation across normal fault complexities - F. Iezzi; M. Francescone; A. Pizzi; A. Blumetti; P. Boncio; P. Di Manna; B. Pace; T. Piacentini; F. Papasodaro; F. Morelli; M. Caciagli; M. Chiappini; et al. (Tectonophysics, 2023)

EPMA maps unveil the actual chemical variations and crystallisation sequence of pyroxene and plagioclase solidified from a basaltic liquid at variable cooling rates - Emanuela Gennaro; Francesco Radica; Gianluca Iezzi; Francesco Vetere; Manuela Nazzari; Georg F. Zellmer; Piergiorgio Scarlato (Chemical Geology, 2023)

Volcano infrasound: progress and future directions - Leighton M. Watson; Alexandra M. Iezzi; Liam Toney; Sean P. Maher; David Fee; Kathleen McKee; Hugo D. Ortiz; Robin S. Matoza; Julia E. Gestrich; Jordan W. Bishop; Alex J. C. Witsil; Jacob F. Anderson; et al. (Bulletin of Volcanology, 2022)
Over the past two decades (2000–2020), volcano infrasound (acoustic waves with frequencies less than 20 Hz propagating in the atmosphere) has evolved from an area of academic research to a useful monitoring tool. As a result, infrasound is routinely used by volcano observatories around the world to detect, locate, and characterize volcanic activity. It is particularly useful in confirming subaerial activity and monitoring remote eruptions, and it has shown promise in forecasting paroxysmal activity at open-vent systems. Fundamental research on volcano infrasound is providing substantial new insights on eruption dynamics and volcanic processes and will continue to do so over the next decade. The increased availability of infrasound sensors will expand observations of varied eruption styles, and the associated increase in data volume will make machine learning workflows more feasible. More sophisticated modeling will be applied to examine infrasound source and propagation effects from local to global distances, leading to improved infrasound-derived estimates of eruption properties. Future work will use infrasound to detect, locate, and characterize moving flows, such as pyroclastic density currents, lahars, rockfalls, lava flows, and avalanches. Infrasound observations will be further integrated with other data streams, such as seismic, ground- and satellite-based thermal and visual imagery, geodetic, lightning, and gas data. The volcano infrasound community should continue efforts to make data and codes accessible and to improve diversity, equity, and inclusion in the field. In summary, the next decade of volcano infrasound research will continue to advance our understanding of complex volcano processes through increased data availability, sensor technologies, enhanced modeling capabilities, and novel data analysis methods that will improve hazard detection and mitigation.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Evolving infrasound detections from Bogoslof volcano, Alaska: insights from atmospheric propagation modeling - Hans F. Schwaiger; John J. Lyons; Alexandra M. Iezzi; David Fee; Matthew M. Haney (Bulletin of Volcanology, 2020)

Infrasound generated by the 2016–2017 shallow submarine eruption of Bogoslof volcano, Alaska - John J. Lyons; Alexandra M. Iezzi; David Fee; Hans F. Schwaiger; Aaron G. Wech; Matthew M. Haney (Bulletin of Volcanology, 2020)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Experimental constraints on the origin of pahoehoe “cicirara” lavas at Mt. Etna Volcano (Sicily, Italy) - F. Vetere; S. Mollo; P. P. Giacomoni; G. Iezzi; M. Coltorti; C. Ferlito; F. Holtz; D. Perugini; P. Scarlato (Bulletin of Volcanology, 2015)

Residual concentrations of the flukicidal compound triclabendazole in dairy cows’ milk and cheese - F. Imperiale; P. Ortiz; M. Cabrera; C. Farias; J.M. Sallovitz; S. Iezzi; J. Pérez; L. Alvarez; C. Lanusse (Food Additives & Contaminants: Part A, 2011)

Effects of 5 Hz subthreshold magnetic stimulation of primary motor cortex on fast finger movements in normal subjects - R. Agostino; E. Iezzi; L. Dinapoli; F. Gilio; A. Conte; F. Mari; A. Berardelli (Experimental Brain Research, 2007)

Synthesis, crystal structure and crystal chemistry of ferri-clinoholmquistite, ?Li2Mg3Fe3+2Si8O22(OH)2 - G. Iezzi; F. Cmara; R. Oberti; G. Della Ventura; G. Pedrazzi; J-L Robert (Physics and Chemistry of Minerals, 2004)

The P21/m? C2/m phase transition in synthetic amphibole Na NaMg Mg5 Si8 O22 (OH)2: thermodynamic and crystal-chemical evaluation - F. Cmara; R. Oberti; G. Iezzi; G. Della Ventura (Physics and Chemistry of Minerals, 2003)

H T -XRD study of synthetic ferrian magnesian spodumene: the effect of site dimension on the P 2 1 / c ? C 2/ c phase transition - F. Cmara; G. Iezzi; R. Oberti (Physics and Chemistry of Minerals, 2003)